Barbershop Communications on Prostate Cancer Screening Using Barber Health Advisers - John S. Luque PhD, MPH; Brian M. Rivers PhD, MPH; Clement K. Gwede PhD, MPH, RN; Maisha Kambon MPH; B. Lee Green PhD; Cathy D. Meade PhD, RN (American Journal of Men's Health, 2011)
Objective: The authors report the outcomes of a community-based, barber health adviser pilot intervention that aims to develop customized educational materials to promote knowledge and awareness of prostate cancer (CaP) and informed decision making about prostate cancer screening (PCS) among a predominantly African American clientele. Method: First, the authors implemented a series of learner verification processes with barbershop clients ( n = 15) to adapt existing CaP health promotion materials. Following intervention implementation in the barbershop, they conducted structured surveys with barbershop clients ( n = 40) to evaluate the intervention. Results: Findings from the posttest showed both a significant increase in barbershop clients’ self-reported knowledge of CaP and in the likelihood of discussing PCS with a health care provider ( p < .001). The client’s cultural model of CaP risk factors revealed cultural consensus (eigenratio = 3.3) and mirrored the biomedical model. All clients surveyed reported positively on the contents of the educational materials, and more than half (53%) had discussed CaP at least twice with their barber in the last month. Conclusion: Based on the pilot results, the barber-administered intervention was an appropriate and viable communication channel for promoting CaP knowledge and awareness in a priority population, African American men.